Les écolieux, nouveaux acteurs des ruralités : enclave de classe ou points d’ancrage pour le renouveau des campagnes ? - Ewa Chuecos (L'Espace Politique)
A new alternative geography of the countryside is emerging through the departures of city dwellers in search of nature and aspiring to live in the territory differently. In the diversity of alternative places within rural areas, the thousand ecovillages already established in France come to question not only metropolitan lifestyles that are destructive of life but also the planning practices of rural communities. The visions of ecology and territory confront and tame each other, which leads us to question the role of these ecovillages within rural territories. Indeed, are ecovillages places that can trigger a demographic, economic and cultural renewal in rural areas perceived as in decline or are they, as some tend to think, class enclaves very well endowed socially, culturally, who came to colonize rural areas ? Through an ethnographic methodology based on immersions of several weeks in 3 ecovillages, participant observation and around twenty biographical interviews, this article will attempt to show both the numerous services offered by ecovillages within the territories but also their difficulties of integration with local communities and rural populations.